Pediatric auricular chondrocytes gene expression analysis in monolayer culture and engineered elastic cartilage - Idrus, Ruszymah; Saim, Lokman; Abdullah, Asma; Sha'ban, Munirah; Chua, Kien Hui; Abdul Latif, Mazlyzam; M. R., Isa; Nor Hussien, Fuzina; Saim, Aminuddin (Elsevier B.V., 2007)
Objectives: This study was aimed at regenerating autologous elastic cartilage for future use in pediatric ear reconstruction surgery. Specific attentions were to characterize pediatric auricular chondrocyte growth in a combination culture medium and to assess the possibility of elastic cartilage regeneration using human fibrin. Study design: Laboratory experiment using human pediatric auricular chondrocytes.Methods: Pediatric auricular chondrocytes growth kinetics and quantitative gene expression profile in three different types of media were compared in primary culture and subsequent three passages. Large-scale culture-expanded chondrocytes from the combination medium were then mixed with human fibrin for the formation of elastic cartilage via tissue engineering technique. Results: The equal mixture of Ham’s F12 and Dulbecco’s Modified Eagle Medium (FD) promoted the best chondrocyte growth at every passage compared to the individual media. Chondrocytes differentiation index; ratio of type II to type I collagen gene expression level, aggrecan and elastin expression gradually decreased while passaging but they were then restored in engineered tissues after implantation. The engineered cartilage was glistening white in color and firm in consistency. Histological evaluation, immunohistochemistry analysis and quantitative gene expression assessment demonstrated that the engineered cartilage resemble the features of native elastic cartilage. Conclusion: Pediatric auricular chondrocytes proliferate better in the combination medium (FD) and the utilization of human fibrin as a biomaterial hold promises for the regeneration of an autologous elastic cartilage for future application in ear reconstructive surgery.